IMPLEMENTASI METODE INDEX CARD MATCH UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI ASMAUL HUSNA DI SD NEGERI 040577 KUTAGERAT - Yahya (Journal of Community Devation, 2025)
This research aims to improve student learning outcomes on Asmaul Husna material using the Index Card Match method in class V of SD Negeri 040577 Kutagerat. The Index Card Match learning method has proven to be effective in improving student learning outcomes and student activity in learning. Classroom action research was conducted with 192 students at SD Negeri 040577 Kutagerat, with a focus on learning Asmaul Husna. The research results showed an increase in the average student test score from cycle I to cycle II. It is recommended that the Index Card Match learning method be adopted by teachers and schools as part of their curriculum to improve student learning outcomes. In cycle I the average was 6.6 at the first meeting and the average was 6.8 at the second meeting, then continued to cycle II with an average of 8.4 at the first meeting and 9.6 at the second meeting. So the average of all meetings is 7.85, thus the average learning outcomes per cycle show a tendency to increase, where in cycle I to cycle II the increase was 2.3.